Vector quantization index coding using LZW algorithm - Yeoh, Wee Soon. (2008)
To develop a new compression algorithm based on the conventional lossless text compression algorithms. The developed algorithm is vector-based lossy and multidimensional generalization of the original text compression algorithm. The compression consists of two stages. First, the test images are segmented into blocks of images.